Deposition of Lead and Cadmium Released by Cigarette Smoke in Dental Structures and Resin Composite - Garcia Takeuchi, Cristina Yoshie [UNESP]; Correa-Afonso, Alessandra Marques; Pedrazzi, Hamilton; Dinelli, Welingtom [UNESP]; Palma-Dibb, Regina Guenka (Wiley-Blackwell, 2011)
Cigarette smoke is a significant source of cadmium, lead, and toxic elements, which are absorbed into the human organism. In this context, the aim of this study was to investigate in vitro the presence of toxic elements, cadmium, and lead deriving from cigarette smoke in the resin composite, dentine, and dental enamel. Eight cylindrical specimens were fabricated from resin composite, bovine enamel, and root dentin fragments that were wet ground and polished with abrasive paper to obtain sections with 6-mm diameter and 2-mm thickness. All specimens were exposed to the smoke of 10 cigarettes/day during 8 days. After the simulation of the cigarette smoke, the specimens were examined with scanning electron microscopy (SEM) and the energy-dispersive X-ray analysis. In the photomicrographic analysis in SEM, no morphological alterations were found; however, the microanalysis identified the presence of cadmium, arsenic, and lead in the different specimens. These findings suggest that the deposition of these elements derived from cigarette smoke could be favored by dental structures and resin composite. Microsc. Res. Tech. 74:287-291, 2011. (C) 2010 Wiley-Liss, Inc.
Keywords: cigarette smoke; lead; cadmium; arsenic; toxicity; dental structures